Language affixation Java in Village Purwosari Subdistrict Tomoni Timur East Luwu Regency - Harsia; Ayu Indriani (Universitas Cokroaminoto Palopo, 2023)
This study aimed to describe the affixation te r so in Java in the village Purwosari District of Tomoni East . This research uses a descriptive method. The subjects of this study were all Javanese vocabulary that experienced affixation. In this study, the authors focused on the functions and meanings of affixes contained in vocabulary. The data were obtained from people who live in the area of Purwosari through documentation techniques, interview techniques , competent listening techniques, note taking techniques, questionnaire techniques, and recording techniques . The results of this study the menu n verifiers indicate the languageIn Java, there are six types of prefixes, namely ( nge - , nya - , per - , ng - , se - , ke - ) There are eight kinds of suffixes, namely ( -ne, -e, -en, -ke, -an, -i, -kan, and was the one ) simulfix there are six kinds of ( all and -ne, per- and -an, nge- and -to, ng- and -Ni, nye- and - to, to- and - en ) . In this study, the authors did not find infix affixes. The meaning of the affix will be formed according to the affix attached to the root word and the function of the affix is ​​to change the type of word from other types of words.